Coastline generator: a tool for generating topographic tessellations around polygons and lines - Lattanzio, Bruno J. (2023)
Many citizen science projects that carry out survey tasks based on location require that the territory to be studied be fragmented into smaller areas with the objectives of, on the one hand, keeping a record of the level of coverage of the regions, and on the other hand, to present spatially bounded objectives to the volunteers of the project. In some cases the sampling areas are related to a terrain feature, such as when surveying the shores of rivers and lakes. Therefore, the aforementioned segmentation must respect the topographical shape of the geographical object to be studied (river or lake).In this work, this type of tessellation is defined as topographic tessellation (TT). Aiming at building the TT, indicating the distance it should have from the shore and the specific measurements of each smaller area is needed. This article presents a framework for the automatic generation of topographic tessellations, which are sets of disjoint and adjacent polygons that form a mosaic following the shape of a georeferenced geometry, and builds a new geographical layer. This tool is useful for spatial-task asignment decision-making.